A novel electrocatalytic filtration system with carbon nanotube supported nanoscale zerovalent copper toward ultrafast oxidation of organic pollutants - Wentian Zheng; Yanbiao Liu; Liu, Wen; Ji, Haodong; Fang Li; Chensi Shen; Xiaofeng Fang; Xiang Li; Xiaoguang Duan (Water Research, 2021)
In this study, we designed an integrated electrochemical filtration system for catalytic activation of peroxymonosulfate (PMS) and degradation of aqueous microcontaminants. Composites of carbon nanotube (CNT) and nanoscale zero valence copper (nZVC) were developed to serve as high-performance catalysts, electrode and filtration media simultaneously. We observed both radical and nonradical reaction pathways, which collectively contributed to the degradation of model pollutants. Congo red was completely removed via a single-pass through the nZVCCNT filter (τ <2 s) at neutral pH. The rapid kinetics of Congo red degradation were maintained across a wide pH range (from 3.0–7.0), in complicated matrixes (e.g., tap water and lake water), and for the degradation of a wide array of persistent organic contaminants. The superior activity of nZVCCNT stems from the boosted redox cycles of Cu2+/Cu+ in the presence of an external electric field. The flow-through design remarkably outperformed the conventional batch system due to the convection-enhanced mass transport. Mechanism studies suggested that the carbonyl group and electrophilic oxygen of CNT served as electron donor and electron acceptor, respectively, to activate PMS to generate •OH and 1O2 via one-electron transport. The electron-deficient Cu atoms are prone to react with PMS via surface hydroxyl group to produce reactive intermediates (Cu2+-O-O-SO3−), and then 1O2 will be generated by breaking the coordination bond of the metastable intermediate. The study will provide a green strategy for the remediation of organic pollution by a highly efficient and integrated system based on catalytic oxidation, electrochemistry, and nano-filtration techniques.
Keywords: Carbocatalysis; Copper; Hydroxyl radical; Peroxymonosulfate; Singlet oxygen